2002
DOI: 10.1159/000048657
|View full text |Cite
|
Sign up to set email alerts
|

Inferior Long-Term Outcome of Renal Transplantation in Patients with Diabetes mellitus

Abstract: Objective: To retrospectively review the long-term outcome of renal transplant in diabetics at Mubarak Al-Kabeer Hospital and Hamad Al-Essa Organ Transplant Center, Kuwait from 1983 to 1998. Methods: There were 631 renal transplant patients, comprising 79 (12.5%) patients with pretransplant diabetes mellitus (pre-TDM), 117 (18.5%) patients with post-transplant diabetes mellitus and 435 (69%) nondiabetics (ND). Subjects with post-transplant diabetes mellitus were excluded from the comparative analysis. Distribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 11 publications
0
4
0
2
Order By: Relevance
“…However, previous comparisons of outcomes in kidney recipients with and without diabetes have yielded conflicting results. Several studies found that the survival rate was lower in kidney transplant recipients with diabetes than in those without diabetes, which was attributed to a high incidence of cardiovascular events [11][12][13][14] , whereas others found no significant differences in patient outcomes [15][16][17][18] . Furthermore, although two previous studies investigated temporal trends in kidney transplant outcomes in patients with and without diabetes, the findings were inconsistent 19,20 .…”
Section: Introductionmentioning
confidence: 99%
“…However, previous comparisons of outcomes in kidney recipients with and without diabetes have yielded conflicting results. Several studies found that the survival rate was lower in kidney transplant recipients with diabetes than in those without diabetes, which was attributed to a high incidence of cardiovascular events [11][12][13][14] , whereas others found no significant differences in patient outcomes [15][16][17][18] . Furthermore, although two previous studies investigated temporal trends in kidney transplant outcomes in patients with and without diabetes, the findings were inconsistent 19,20 .…”
Section: Introductionmentioning
confidence: 99%
“…Together, the findings regarding the greater likelihood of developing PTDM, greater number of antidiabetic medications, and higher fasting blood glucose measures suggest that elderly recipients may experience greater difficulty in controlling their diabetes mellitus than younger recipients. Because research indicates that pre‐ and posttransplant diabetes mellitus adversely affect patient survival, 31–33 elderly recipients' blood glucose levels and response to antidiabetic therapy should be closely monitored and treated appropriately to prevent adverse health outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…При СД дислипидемия рассматривается как следствие основного заболевания, особенно в условиях неадекватного контроля гликемии и целого ряда сопутствующих факторов -возраста, избыточной массы тела и ожирения, поражения почек и т.д. При изучении параметров липидного спектра у пациентов после АТП, дислипидемия достоверно чаще наблюдалась у пациентов с СД -в 37% случаев, чем у пациентов без диабетатолько в 6% [14]. Коррекция нарушений липидного обмена сохраняет важное значение после АТП для профилактики прогрессирования гломерулосклероза.…”
Section: сахарный диабетunclassified